Modified polypropylene fiber, modified polypropylene fiber reinforced cement-based material and preparation method of modified polypropylene fiber reinforced cement-based material

By coating graphene oxide on the surface of PP fibers, the binding force with the cement matrix is ​​enhanced, and the problem of insufficient binding between PP fibers and cement matrix is ​​solved, which significantly increases the early mechanical strength of FRCC and the amount of PP fibers.

CN119877268APending Publication Date: 2025-04-25SHANDONG JIAOTONG UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510062181.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The combination of existing PP fibers and cement matrix is ​​weak, resulting in easy formation of cracks under high usage, affecting the overall performance of the composite material.

Method used

By coating a layer of graphene oxide on the surface of the PP fiber, the bonding force between the interface between the PP fiber and the cement matrix is ​​significantly enhanced, the amount of PP fiber is added, and the early mechanical strength of FRCC is enhanced.

Benefits of technology

The binding force between PP fiber and cement matrix is ​​significantly improved, the early mechanical strength of FRCC is improved, and the amount of PP fiber is increased, solving the problem of insufficient bonding between fiber and cement matrix.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877268A_ABST
    Figure CN119877268A_ABST
Patent Text Reader

Abstract

The invention discloses a modified polypropylene fiber, a modified polypropylene fiber reinforced cement-based material and a preparation method of the modified polypropylene fiber reinforced cement-based material, and belongs to the field of material science and surface technology. The flaky GO is prepared on the surface of the PP fiber by adopting a physical coating method, heating equipment is not needed in the surface modification process, the steps are simple, the operation is convenient, resources are not consumed, and the method is suitable for batch production. The surface-modified PP fiber has excellent mechanical properties and electrical conductivity. According to the modified polypropylene fiber reinforced cement-based material provided by the invention, the flaky GO modified PP fiber material is adopted, and the flaky GO can promote full fusion reaction of PP fibers and cement aggregate, so that the cohesiveness between the PP fibers and cement is improved, and the mechanical property of the FRCC material prepared by the invention is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material science and surface technology, and specifically relates to a modified polypropylene fiber, a modified polypropylene fiber reinforced cement-based material and a preparation method thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Cement-based materials are popular in engineering applications for their controllable strength and excellent durability. However, their brittleness and shrinkage limit wider applications. In order to overcome these defects, fiber-reinforced cement-based composites (FRCC) came into being, using fibers as a bridge for crack deflection, absorbing fracture energy, and preventing crack generation and expansion through the fiber network, thereby significantly improving the toughness, flexural strength and tensile strength of FRCC. Among a variety of engineering fibers, PP fiber has become an ideal choice for strengthening the cement matrix and improving crack resistance due to its low cost, light weight, corrosion resistance, high strength and high toughness.

[0004] At present, a large number of used masks are thrown away or landfilled without any treatment or proper disposal, which poses a major risk to the natural environment. The secondary utilization of discarded masks is also an urgent problem to be solved. Medical masks are usually made of polypropylene or polyester non-woven fabrics for the skin contact layer, and melt-blown ultrafine polypropylene fibers for the filter layer. Extracting polypropylene fibers from discarded masks for FRCC research can help reduce the environmental risks caused by discarded masks and save energy and reduce emissions. However, the chemical stability and chemical inertness of PP fibers lead to weak bonding with the cement matrix. At high dosages (>0.3wt%), cracks are easily formed around the fibers, affecting the overall performance of the composite material.

[0005] To improve the surface properties of polymer fibers, a variety of surface treatment techniques have been developed, including flame treatment, ion / plasma beam treatment, and chemical / physical coating techniques, to increase the roughness or chemical activity of the fiber surface and improve its bonding with the cement matrix. However, these methods have not been widely used in large-scale fiber treatment due to the complexity of processing or the possibility of irreversible damage to the fibers. In contrast, simple surface coating methods can achieve the desired surface properties while avoiding the above disadvantages.

[0006] In recent years, carbon nanomaterials, such as carbon nanotubes, carbon nanofibers, and graphene derivatives, have been widely used to reinforce cementitious composites or as new coating materials for low surface energy fibers due to their excellent mechanical properties and large specific surface area. Graphene oxide (GO), as one of the popular materials, is easily dispersed in water due to its negatively charged oxygen functional groups on the edges and basal planes of the sheets, and reacts chemically with cement hydrates through covalent bonds, promoting the formation of more regular hydration products and denser microstructures, while inhibiting the propagation of microcracks, showing its potential as a nano-reinforcement material. However, there are no reports on combining PP fibers and graphene oxide to improve the performance of FRCC. Summary of the invention

[0007] In order to overcome the deficiencies of the prior art, the purpose of the present invention is to provide a modified polypropylene fiber, a modified polypropylene fiber reinforced cement-based material and a preparation method thereof. The present invention significantly enhances the bonding force between the PP fiber and the cement matrix interface by coating a layer of graphene oxide on the surface of the PP fiber, increases the amount of PP fiber added, and improves the early mechanical strength of FRCC, thereby providing an effective surface modification scheme for the application of PP fiber in cement concrete.

[0008] In order to achieve the above object, the technical solution of the present invention is:

[0009] A first aspect of the present invention provides a modified polypropylene fiber, wherein the modified polypropylene fiber is a polypropylene fiber with flaky graphene oxide grafted on the surface.

[0010] The present invention provides a modified polypropylene fiber, the core feature of which is that graphene oxide is used as a surface modifier, and graphene oxide is grafted on the surface of PP fiber with its unique flake form to achieve modification. Through this modification method, the surface properties of PP fiber are significantly improved, and the bonding force between PP fiber and cement matrix is ​​enhanced, thereby improving the overall performance of cement-based composite materials, while also increasing the amount of PP fiber used.

[0011] It should be noted that the PP fiber used in the present invention can be derived from industrial synthesis or extracted from waste masks, providing an environmentally friendly and efficient material recycling method for waste masks. Through modification, not only the practicality of polypropylene fiber is improved, but also the concept of sustainable development and environmental protection is responded to.

[0012] In some embodiments of the present invention, the modified polypropylene fiber has a length of 10-15 mm and a diameter of 20-30 μm.

[0013] Preferably, the length of the modified polypropylene fiber is 12 mm and the diameter is 25 μm. The FRCC prepared by using the modified polypropylene fiber of this size has good performance.

[0014] In some embodiments of the present invention, the content of graphene oxide in the modified polypropylene fiber is 0.01 L / m 2 .

[0015] The second aspect of the present invention provides a method for preparing the modified polypropylene fiber, comprising:

[0016] The graphene oxide solution is brought into contact with the polypropylene fiber and dried to obtain modified polypropylene fiber.

[0017] It should be noted that the graphene oxide can be applied to the surface of the polypropylene fiber by spraying or soaking. Specifically, in some embodiments of the present invention, contacting the graphene oxide solution with the polypropylene fiber includes:

[0018] The graphene oxide solution is sprayed on the polypropylene fiber at a spraying speed of 0.1-0.5 L / min; the spraying angle is 30-50°; the horizontal distance between the nozzle and the polypropylene fiber is 15-20 cm, preferably 18 cm; the vertical distance is 15-20 cm, preferably 18 cm.

[0019] In some embodiments of the present invention, contacting the graphene oxide solution with the polypropylene fiber comprises: placing the polypropylene fiber in the graphene oxide solution, stirring for 10-20 minutes, and soaking for 2-3 hours.

[0020] In some embodiments of the present invention, the concentration of the graphene oxide solution is 1-3 mg / mL, preferably 2 mg / mL; the solvent of the graphene oxide solution is water.

[0021] In some embodiments of the present invention, the drying is performed at 50-100° C. for 3-8 h, preferably at 80° C. for 5 h.

[0022] The third aspect of the present invention provides a modified polypropylene fiber reinforced cement-based material, which comprises the following components by weight:

[0023] 5-6 parts of cement, 1 part of fly ash, 3-4 parts of quartz sand, 0.01-0.02 parts of water reducer, 2 parts of water;

[0024] The modified polypropylene fiber reinforced cement-based material also includes the modified polypropylene fiber mentioned above or the modified polypropylene fiber prepared by the above preparation method, and the dosage of the modified polypropylene fiber is 0.1-2% of the mass of cement.

[0025] In some embodiments of the present invention, the water reducer includes any one of a polycarboxylate water reducer, a polyurethane water reducer and a polyhydroxyethylene water reducer.

[0026] In some embodiments of the present invention, the particle size of the quartz sand is 110-160 mesh.

[0027] In some embodiments of the present invention, the following components are included by weight:

[0028] 5.6 parts of cement, 1 part of fly ash, 3.3 parts of quartz sand, 0.016 parts of water reducer, and 2 parts of water; the amount of the modified polypropylene fiber is 2% of the mass of the cement.

[0029] A fourth aspect of the present invention provides a method for preparing the modified polypropylene fiber reinforced cement-based material, comprising:

[0030] Cement, fly ash, quartz sand, water and water reducing agent are mixed and stirred at a speed of 100-150 r / min for 150-200 s, and modified polypropylene fiber is added at a speed of 5-15 g / min and stirred to obtain modified polypropylene fiber reinforced cement-based material.

[0031] In some embodiments of the present invention, the modified polypropylene fiber is added at a rate of 10 g / min.

[0032] The beneficial effects of the present invention are:

[0033] The present invention prepares flake graphene oxide on the surface of polypropylene fiber, and the whole treatment process can be carried out at room temperature, the operation is simple and convenient, and no large-scale instruments and equipment are required.

[0034] Compared with the traditional process technology, the present invention has the following beneficial effects:

[0035] The present invention adopts a physical coating method to prepare sheet GO on the surface of PP fiber. No heating equipment is required during the surface modification process. The steps are simple, the operation is convenient, and no resources are consumed. It is suitable for mass production. The surface-modified PP fiber has excellent mechanical properties and conductive properties.

[0036] The modified polypropylene fiber reinforced cement-based material provided by the present invention adds PP fiber material modified by flaky GO, and the flaky GO can promote the full fusion reaction of PP fiber and cement aggregate, improve the adhesion between PP fiber and cement, improve the mechanical properties of the FRCC material prepared by the present invention, especially the early mechanical strength of FRCC, and also increase the amount of PP fiber. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0038] Figure 1The self-made conductivity testing device in Example 1 of the present invention;

[0039] Figure 2 The XRD diffraction patterns of PP fibers before and after GO modification in Example 1 of the present invention;

[0040] Figure 3 is the infrared spectrum of PP fiber before and after GO modification in Example 1 of the present invention;

[0041] Figure 4 The morphology of PP fiber (sprayed) after GO modification in Example 1 of the present invention;

[0042] Figure 5 The morphology of PP fiber (impregnated) after GO modification in Example 2 of the present invention;

[0043] Figure 6 The early mechanical strength of the FRCC specimens with unmodified and GO-modified PP fibers added in Example 1 of the present invention;

[0044] Figure 7 The conductive properties of the FRCC specimens with unmodified and GO-modified PP fibers added in Example 1 of the present invention are shown. DETAILED DESCRIPTION

[0045] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0046] Example 1

[0047] (1) Mask breakage: Collect discarded masks, sort them, cut off the nose clip and ear clips with scissors, and cut the masks into 6mm 2 The fragments are placed in a household wall breaking machine and sheared for 15 seconds to obtain mask fiber filaments, namely PP fibers.

[0048] (2) Spraying GO on PP fibers: A 2 mg / mL graphene oxide solution was placed in a spray bottle. The PP fibers were fixed on aluminum foil. The spray bottle was adjusted to an atomized state with a spray rate of 0.2 L / min, a spray angle of 40°, a distance from the nozzle to the PP fiber of 15 cm-20 cm, and a height of 15 cm-20 cm from the spray bottle nozzle to the test bench. The mixture was left to stand for 2 min. The PP fibers grafted with flake graphene oxide were obtained by oven drying.

[0049] (3) Fabrication and compressive performance testing of FRCC specimens:

[0050] 1. Matrix mix ratio: Weigh 1062g P·O 42.5 grade ordinary Portland cement, 188g first-grade fly ash, 625g 110-160 mesh quartz sand, and 3.125g high-performance polycarboxylate water-reducing agent at a water-binder ratio of 0.3 and a sand-binder ratio of 0.58.

[0051] 2. Add cement, fly ash, quartz sand, water and water reducing agent into cement mortar mixer in sequence, stir at 137r / min at room temperature for 180s, add 21.24g PP fiber grafted with flake graphene oxide in step 1 into the mixer at a speed of 10g / min and stir for 240s, mix and stir evenly for 330s, put into a 40mm×40mm×160mm mold and vibrate for 120s to obtain FRCC specimens, and cure them to 3d, 5d, 7d and 28d to be tested respectively.

[0052] Comparative Example 1

[0053] The difference from Example 1 is that the step of "(2) spraying GO on PP fibers" is omitted, and the remaining steps are consistent with those of Example 1 to obtain a FRCC specimen.

[0054] Performance test of FRCC specimens obtained in Example 1 and Comparative Example 1

[0055] 1. Characterization: The physical phase of PP fibers before and after grafting with flaky graphene oxide was tested by X-ray diffractometer (XRD, D8 Advance, Bruker), the functional groups of PP fibers before and after grafting with flaky graphene oxide were tested by Fourier transform infrared spectrometer (FTIR, IS50, Nicolet), and the surface morphology of PP fibers grafted with flaky graphene oxide was characterized by field emission electron microscopy (FE-SEM, Sigma 800, Zeiss).

[0056] Figure 2 is the XRD diffraction pattern of PP fiber before and after GO modification in Example 1 of the present invention, Figure 3 is the infrared spectrum of PP fiber before and after GO modification in Example 1 of the present invention, Figure 4 This is the morphology of PP fiber (sprayed) after GO modification in Example 1 of the present invention. Figure 2 , 3 , 4 can be confirmed that flake graphene oxide was successfully grafted on the surface of PP fiber.

[0057] 2. Strength test: Referring to the "Test Method for Strength of Cement Mortar" GB / T 17671-2021, the 3d, 5d, and 7d compressive strength of the test specimens were tested, and the compressive strength test of the FRCC specimens obtained in Example 1 and Comparative Example 1 was carried out on a cement compression and flexural testing machine.

[0058] Test results such as Figure 6 As shown, the compressive strength of the FRCC specimen added with PP fibers grafted with flake graphene oxide in step 1 is higher than that of the FRCC specimen added with unmodified PP fibers, and the early strength of the FRCC specimen is significantly improved.

[0059] 3. Fabrication of FRCC specimens and conductivity performance test

[0060] (1) Preparation of test specimens The difference between the preparation method of FRCC test specimens in step (3) of Example 1 is that the test specimen mold is 40 mm×40 mm×40 mm, and a copper mesh is pre-buried, and the other steps are the same. The test specimens are cured for 28 days.

[0061] (2) Use the series connection method to measure the current. The experimental setup is as follows: Figure 1 .

[0062] (3) Use formula 1 to calculate its resistance, and use formula 2 to calculate its conductivity.

[0063]

[0064] Among them, U is voltage; I is DC current

[0065]

[0066] Where L is the distance between the two electrodes; S e is the electrode surface area; R is the DC resistance.

[0067] Test results such as Figure 7 As shown, the conductivity of the FRCC specimen prepared in Example 1 is significantly improved compared with the FRCC specimen prepared in Comparative Example 1.

[0068] Example 2

[0069] (1) Mask breakage: Collect discarded masks, sort them, cut off the nose clip and ear clips with scissors, and cut the masks into 6mm 2 Place the fragments into a household wall breaking machine and cut them for 15 seconds to obtain mask fiber filaments.

[0070] (2) PP fiber surface soaked with GO:

[0071] Put 2g of mask fiber into 15g of prepared graphene oxide solution with a concentration of 2mg / mL, place the beaker containing the mixed solution on a magnetic stirrer and stir for 15min, soak at room temperature for 2-3h, and after soaking, dry it in an oven at 80° for 5h to obtain the modified PP fiber.

[0072] (3) Testing of modified materials: The physical phase of the PP fibers before and after modification was tested by X-ray diffractometer (XRD, D8 Advance, Bruker), the functional groups of the PP fibers before and after modification were tested by Fourier transform infrared spectrometer (FTIR, IS50, Nicolet), and the surface morphology of the modified PP fibers was characterized by field emission electron microscopy (FE-SEM, Sigma 800, Zeiss).

[0073] The present invention uses FE-SEM to characterize the surface morphology of the modified PP material in Example 2 ( Figure 5 ), it can be seen that there is flaky GO material attached to the surface of PP fiber.

[0074] Example 3

[0075] (1) Purchase PP fiber and soak it in GO: Put the purchased PP fiber with a length of 12 mm into 15 g of graphene oxide solution with a concentration of 2 mg / mL, place the beaker containing the mixed solution on a magnetic stirrer and stir for 15 min, soak it at room temperature for 2-3 h, and after soaking, dry it in an oven at 80° for 5 h to obtain the modified PP fiber.

[0076] (3) Testing of modified materials: The physical phase of the PP fibers before and after modification was tested by X-ray diffractometer (XRD, D8 Advance, Bruker), the functional groups of the PP fibers before and after modification were tested by Fourier transform infrared spectrometer (FTIR, IS50, Nicolet), and the surface morphology of the modified PP fibers was characterized by field emission electron microscopy (FE-SEM, Sigma 800, Zeiss).

[0077] After testing, the PP fibers obtained in Example 2 and Example 3 were successfully loaded with flake graphene oxide on their surfaces. The modified PP fibers obtained in Example 2 and Example 3 were used to prepare FRCC specimens, and the early mechanical strength and electrical conductivity of the specimens were also improved.

[0078] In addition to the above experiments, the present invention also screened the types of fibers, and used polypropylene fibers, carbon fibers, steel fibers and glass fibers to load flaky graphene oxide using the method of Example 1 to prepare FRCC specimens. It was found that only when polypropylene fibers were used, the early strength of the obtained FRCC specimens was improved. The 7-day compressive strength of the FRCC specimens prepared using other fibers grafted with graphene oxide was only between 30 and 35 MPa, which was much lower than the 7-day compressive strength of the FRCC specimen of Example 1 of the present invention (51.6 MPa).

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A modified polypropylene fiber, characterized in that: The modified polypropylene fiber is a polypropylene fiber with flake graphene oxide nanoparticles grafted on the surface.

2. The modified polypropylene fiber according to claim 1, characterized in that The modified polypropylene fiber has a length of 10-15 mm and a diameter of 20-30 μm; Preferably, the modified polypropylene fiber has a length of 12 mm and a diameter of 25 μm; Preferably, the content of graphene oxide in the modified polypropylene fiber is 0.01 L / m 2 .

3. A method for preparing modified polypropylene fiber according to claim 1 or 2, characterized in that: include: The graphene oxide solution is brought into contact with the polypropylene fiber and dried to obtain modified polypropylene fiber.

4. The preparation method according to claim 3, characterized in that: The step of contacting the graphene oxide solution with the polypropylene fiber comprises: The graphene oxide solution is sprayed on the polypropylene fiber at a spraying speed of 0.1-0.5 L / min; the spraying angle is 30-50°; the horizontal distance between the nozzle and the polypropylene fiber is 15-20 cm, preferably 18 cm; the vertical distance is 15-20 cm, preferably 18 cm; Alternatively, place the polypropylene fiber in the graphene oxide solution, stir for 10-20 minutes, and soak for 2-3 hours; Preferably, the concentration of the graphene oxide solution is 1-3 mg / mL, preferably 2 mg / mL; the solvent of the graphene oxide solution is water; Preferably, the drying is carried out at 50-100°C for 3-8h, preferably at 80°C for 5h.

5. A modified polypropylene fiber reinforced cement-based material, characterized in that: In terms of weight fraction, it includes the following components: 5-6 parts of cement, 1 part of fly ash, 3-4 parts of quartz sand, 0.01-0.02 parts of water reducing agent, and 2 parts of water; The modified polypropylene fiber reinforced cement-based material further comprises the modified polypropylene fiber according to claim 1 or 2 or the modified polypropylene fiber prepared by the preparation method according to claim 3 or 4, and the dosage of the modified polypropylene fiber is 0.1-2% of the mass of cement.

6. The modified polypropylene fiber reinforced cement-based material according to claim 5, characterized in that: The water reducer includes any one of a polycarboxylate water reducer, a polyurethane water reducer and a polyhydroxyethylene water reducer.

7. The modified polypropylene fiber reinforced cement-based material according to claim 5, characterized in that: The particle size of the quartz sand is 110-160 meshes.

8. The modified polypropylene fiber reinforced cement-based material according to any one of claims 5 to 7, characterized in that: In terms of weight fraction, it includes the following components: 5.6 parts cement, 1 part fly ash, 3.3 parts quartz sand, 0.016 parts water reducer, 2 parts water; The modified polypropylene fiber is added in an amount of 2% of the mass of cement.

9. A method for preparing a modified polypropylene fiber reinforced cement-based material according to any one of claims 5 to 8, characterized in that: include: Cement, fly ash, quartz sand, water and water reducing agent are mixed and stirred at a speed of 100-150 r / min for 150-200 s, and modified polypropylene fiber is added at a speed of 5-15 g / min and stirred to obtain modified polypropylene fiber reinforced cement-based material.

10. The preparation method according to claim 9, characterized in that: The modified polypropylene fiber is added at a speed of 10 g / min.

Citation Information

Cited By

  • Conductive fiber reinforced concrete and preparation method thereof

    CN120365013A

  • Electrically conductive fiber reinforced concrete and method for producing the same

    CN120365013B